Indigenous Entrepreneurship and Sports Development in Post-Colonial Lagos: The Israel Adebajo and Flaming Flamingo Story - JIMOH, Mufutau Oluwasegun (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
The transformation of Lagos from a fishing economy in the pre-colonial era to a sprawling and economically vibrant mega-city in the post-colonial period owes much to the agency of indigenous political mobilisers, merchants, entrepreneurs, proponents of religions, sports patrons, arts, and educationists, among other personalities whose life histories intertwine with the ideals of the city. This essay explores the contributions of Israel Adebajo, one of the figures who transformed the social and economic skyline of Lagos after independence. Israel Adebajo was an entrepreneur, a sports enthusiast and patron, and a socialite, who was one of the drivers of the development of football in Lagos in the second half of the 20th century. This essay argues that, like many other individual change agents, whose footprints appear fleetingly in the historiography of the development of the city, the contributions of Israel Adebajo, particularly in the context of football, are waiting to be written into the history of Lagos in the 20th century, and as a testament to the significance of biographies in the construction of micro-history.